IMPLEMENTASI PERATURAN DAERAH NOMOR 9 TAHUN 2015 DALAM PENGANGKATAN PENJABAT PENGHULU DI KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR - Suryani, Suryani; Irawati, Irawati; Ferizko, Adia (Jurnal Ilmiah Publika, 2023)
Implementation of Regional Regulation Number 9 of 2015 in the Appointment of Acting Penghulu in Bangko Pusako District, Rokan Hilir Regency, which aims to find out whether Regional Regulation No. 9 of 2015 is implemented well or vice versa. The theory used is policy implementation (Van Horn and Van Metter in Kurniawan: 2020). It can be seen in six indicators, namely: policy standards and targets, resources, characteristics of implementing organizations, attitudes of implementers, communication between organizations, and the social, economic, and political environment. This research uses qualitative research methods and is analyzed based on qualitative descriptive methods. The results of this research can be concluded that the implementation of Regional Regulation Number 9 of 2015 in the Appointment of Acting Penghulu in Bangko Pusako District, Rokan Hilir Regency, has not been implemented properly. This is because communication is less effective. As well as the attitude of implementers that is inconsistent with established policies. So there is a need for effective communication and deliberation between the regional governments that have the authority to appoint officials and have a consistent attitude towards the established policies.